Effects of environmental and anthropogenic determinants on changes in groundwater levels in selected peat bogs of Slowinski National Park, northern Poland - Chlost, Izabela; Cieśliński, Roman (Instytut Geologii UAM, 2018)
The present study focuses on two Baltic-type peat bogs in Slowinski National Park, namely that at Żarnowskie and at Kluki, located in the Lake Łebsko catchment and both characterised by a centrally located dome with a very marshy fringe area featuring an emerging marshy coniferous forest (Vaccinio uliginosi-Pinetum). The Żarnowskie bog is under active protection. A total of 24 flow barriers were installed in drainage ditches during the years 2006 and 2007. The purpose of these barriers was to put a halt to water outflow. In addition, 30 hectares of young pine forest were cleared in order to decrease loss of water via evapotranspiration. Kluki peat bog is only partially protected by Polish law. The lack of efforts to prevent outflow via the canal is due to the fact that the canal is utilised to drain meadows in the vicinity of the village of Łokciowe outside of the national park. Peat formation no longer occurs in this peat bog. The hydrological condition of the bog is catastrophic as a result of its main canal, referred to as Canal C9, which is 2.5 to 3.0 m deep and 10 m wide in places. Both peat bogs are monitored for fluctuations in groundwater. Research has shown that changes in water levels fluc- tuate based on season of the year and geographical location, which is illustrated quite well using the two studied peat bogs. The water retention rate of the Żarnowskie peat bog may be considered fairly high and is likely to improve due to pro- tective measures enabled by Polish environmental laws. The water retention rate of the bog is consistently improving thanks to these measures, fluctuations in water level are small and the water level does not drop under 0.5 m below ground level even under extreme hydrometeorological conditions. This yields optimum conditions for renewed peat formation in this area. One potential threat is the Krakulice peat extraction facility, which is located in the southern part of the bog close to the boundary with the national park.
Keywords: wetland; retention; piezometer; drainage system; protection